Equity-based crowd funding project: affect on social capital / Sentot Imam Wahjono … [et al.] - Wahjono, Sentot Imam; Marina, Anna; Fam, Soo Fen; Hasan, Asriani (Universiti Teknologi Mara Selangor, 2020)
The aim of this research is to determine the social capital that can affect the success rate of the equity-based crowdfunding project and which is the most influential factor towards the success rate of an equity-based crowdfunding project. Hence, the researcher uses the descriptive to design quantitative questionnaires. It consists of the social network, obligation and shared meaning. Thus, three independent variables will be proceeding by distributing questionnaire online. The researcher will use Google Form as one of the tools to distribute a questionnaire and collect back 267 respondents from online. After collect data, only 167 respondents involved in this research. Pearson's correlation and multiple regression use to test the relationship and significant effect between the independent variable and dependent variable. Through the statistic of SPSS, it was found the research objective was achieved when the hypothesis of three-factor for the successfulness of equity-based crowdfunding is proving.